PENGARUH MEDIA AUDIO VISUAL TERHADAP MOTIVASI BELAJAR IPA SISWA KELAS V SDN KAPOPO - Azizah Azizah; Nurul Fatimah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This study aims to determine the effect of Audio Visual Media on students' motivation to learn science. This type of research is a quasi-experimental design with One Group pretest-posttest design. This research was conducted in class V SDN Kapopo. The instrument used in this research is a questionnaire to measure students' motivation to learn science. Data analysis consisted of validity, reliability, normality test and t-test used to test the research hypothesis assisted by the SPSS 25 program. The results showed that Audio Visual media had an effect on students' motivation to learn science. This can be seen from the acquisition of the value of sig < which is 0.000 < 0.05 at a significance level of 5% so that Hₒ is rejected and Hₐ is accepted. So it can be concluded that the use of audio-visual media has an effect on the motivation to learn science for fifth graders at SDN Kapopo.